PEMANFAATAN AUGMENTED REALITY SEBAGAI TOMBOL VIRTUAL UNTUK MELATIH DAYA INGAT SISWA TK - Olivia Suryanto Jao; Abdul Munir S.; Hamdan Arfandy (KHARISMA Tech, 2018)
This research is motivated children’s ability in remembering, is the augmented reality as a virtual button can be used or not. The method used is descriptive method. The experiment was done 3 times, result of first experiment calculation indicates average student’s memory on the indicator undeveloped 20%, began to develop 40%, evolve as expected 0%, and evolve very good 40%. Second experiment undeveloped 0%, began to develop 20%, evolve as expected 40%, and evolve very good 40%. The third experiment shows undeveloped 0%, began to develop 0%, evolve as expected 20%, and evolve very good 80%. Based on the data that has been obtained, showing that there is an increase ability memory.